MODEL KEPEMIMPINAN PENDIDIKAN DALAM MENINGKATKAN KINERJA ORGANISASI SEKOLAH: TINJAUAN LITERATUR - Muhammad Hasan Basari; Muqtafi Ahmad Fahmi; Ravizal (CV. Adiba Aisha Amira, 2026)
This article aims to analyze various educational leadership models and their contribution to improving school organizational performance based on a literature review. Various studies indicate that transformational leadership, instructional leadership, and distributive leadership play a significant role in promoting school effectiveness. Through a literature synthesis, this article finds that the principal's role as a leader is a key factor in developing school culture, increasing teacher motivation, and achieving educational goals